Punctuations in a Poetic Translation from Russian to Polish (on the Example of Analyses of Mandelshtam’s Poetry) - Цуркан-Дружка, Элона (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The article focuses on the role of punctuation marks in a poetic text and the difficulties associated with their reproduction in translation. The author analyzes the Polish version of O. Mandelstam’s poem Peterburgskie strofy and concentrate attention on the differences between level of emotions in the original and translation. Substitutions introduced in the grammatical system of the work, in certain cases, have a significant impact on the emotional and semantic level of the poem. At the end of the article, the question is raised about the translation strategy chosen by the author of the translation.